Forests and the Malays: Historical Perspective on the Forest Management in Sumatera (Indonesia) - Mohammad Fathi Royyani; Ary Prihardhyanto Keim; Ida Farida Hasanah; Wawan Sujarwo (The Ethnobiological Society of Indonesia, 2021)
The study figured out dynamic interactions between forests and the Malays in Sumatera (i.e. Riau Province), Indonesia. The interactions observed in this study indicate that in many cases human activities resulted in a direct impact on forest degradation, but at the same time some people have fought to protect the forests. This study also revealed that the forest is undeniable natural resources. Even though the forest is susceptible to human activities because it can easily be explored. History had shown from colonial to independence that forest is an important resource to contribute to state foreign exchange, due to business permit issued by the government for companies to manage natural forests. Somehow, that policy impacted on forest degradation quickly. In every period, the pressure to protect forests is always accompanied by the state’s policy. The interactions between humans and forests are mostly affected by external factors, including trading natural resources for economic interest.